Fostering Team Innovation: Why Is It Important to Combine Opposing Action Strategies? - Gebert, Diether; Boerner, Sabine; Kearney, Eric (Organization Science, 2010)
We develop a framework that provides a general theoretical rationale for the claim made by several authors that combining opposing action strategies fosters team innovation. We distinguish between open and closed strategies and posit that these are opposing but complementary in that each fosters one of two processes necessary for team innovation: open action strategies (e.g., delegative leadership) promote knowledge generation, and closed action strategies (e.g., directive leadership) enhance knowledge integration. We argue that each pole of a pair of opposing action strategies both energizes and detracts from elements of innovation. Thus, it could be expected that combining opposing action strategies leads to an impasse, as the negative effects of each strategy might offset the positive effects of the opposite strategy. There is currently no viable explanation in the literature for why this mutual neutralization may not occur. We aim to fill this gap by explicating why and how opposing action strategies, when implemented simultaneously, do not countervail each other's positive effects, but rather yield positive synergies that fuel team innovation.